Vaccination promotion as a responsibility of the Russian authorities - A. V. Basova; G. N. Komkova; E. N. Toguzaeva (Журнал инфектологии, 2025)
Introduction. An analytical review of regulatory legal acts and scientific literature on the problem of public adherence to vaccination prevention and the development of positive vaccination propaganda in Russia has been conducted.The article examines the implementation of vaccination propaganda in Russia as the most important tool for psychological influence on public commitment to active immunoprophylaxis of infectious diseases, as well as the powers of Russian authorities to carry out such propaganda. The reasons that prevent citizens from realizing the need for vaccination and ways to overcome “vaccination nihilism” are identified.Materials: scientific publications and national regulatory legal acts on this issue.Methods: general analytical methods of cognition (analysis, synthesis, generalization) made it possible to comprehensively consider the socio-legal validity of vaccination propaganda in Russia; a formal legal method consisting in the analysis of current legal norms, legal concepts and definitions, which became the basis for the study of legal norms governing the specifics of vaccination propaganda by government officials, health workers and the leaders of public opinion, and also allowed to propose measures to improve legislation on this issue.Results. The fragmentation of vaccination propaganda by authorities and public organizations, the imperfection of its legal regulation, the absence of responsible government authorities for its implementation, as well as the positive relationship between vaccination propaganda and the coverage of the population by active immunoprophylaxis of diseases has been established.Conclusion. Solving the identified problems in the mechanism of vaccination promotion in Russia by the authorities, as well as providing the Russian population with up-to-date information based on the results of evidence-based medicine about the benefits and minor risks of vaccination, will contribute to a more effective implementation of the authorities’ powers to create a culture of responsible attitude of citizens to their health.